2009
DOI: 10.3758/brm.41.4.1169
|View full text |Cite
|
Sign up to set email alerts
|

Home cage testing of delay discounting in rats

Abstract: Testing rodents in their home cages has become increasingly popular. Since human intervention, handling, and transport are minimized, behavior can be recorded undisturbed and continuously. Currently existing home cage systems are too complex if only relatively simple operant-learning tests are to be carried out in rats. For that purpose, a new low-cost computer-controlled operant panel was designed, which can be placed inside the home cage. A pilot study was carried out, using an intolerance-to-delay protocol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…a low odds value) if subjects are paced to very long mITI (e.g. Koot et al, 2009), while it would be perceived as much more frustrating (i.e. equivalent to higher odds values) if subjects are paced to quite a shorter mITI, as in the present study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…a low odds value) if subjects are paced to very long mITI (e.g. Koot et al, 2009), while it would be perceived as much more frustrating (i.e. equivalent to higher odds values) if subjects are paced to quite a shorter mITI, as in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Koot et al, 2009). In summary, even though a further and deeper validation should be carried out, we propose that the concept of delay-equivalent odds values may allow to compare ID task results across various studies, differing for objective (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that male and female rats and humans often differ in their performance on tasks measuring impulsivity (e.g., Anker et al 2008; Bayless et al 2012; Bayless et al 2015; Koot et al 2009a; Marsh et al 2002). Despite our knowledge that impulsive choice contributes to maladaptive behaviors, current understanding of female rodent choice behavior is sparse, as most work investigating the mechanisms of various behaviors has been conducted in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Females that did not adapt to the IntelliCage (no drinking for at least 36 h during habituation) were removed from the cage and excluded from testing. For training on the DDT 47 , all doors were opened and females had free access to water and saccharine in each corner (0 s delay). DDT started when preference to saccharine was established (450% saccharine licks over all licks).…”
Section: Methodsmentioning
confidence: 99%